Fibrin Glue as an alternative to Microsuture Technique in brachial Plexus and peripheral nerve Injuries (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To compare the outcome of Fibrin glue with micro suture technique for the treatment of Brachial plexus and peripheral nerve injuries.Methods: This randomized control trial was conducted at Military Hand Surgery Centre in Lahore Pakistan from July 2015 to December 2017. We managed 70 cases with brachial plexus and peripheral nerve injuries fulfilling the inclusion criteria in two groups. One repaired with fibrin glue(group A) and other with microsuture(group B) with follow up of one and half year. Outcomes were measured as convenience of the surgeon, duration of surgery and efficacy in the form of motor recovery. Post stratification Chi square test and independent sample t tests were applied to important variables taking P value of ? 0.05 as significant.Results: A total of 70 patients were equally divided in two groups A and B (35 each).The mean age of group A patients were 34.37 ±8.23 and group B was 33.89 ±9.13.Brachial plexus injuries(BPI) were noted in 18( 25.7% ) patients in group A and 15(21.4% ) patients in group B. Peripheral nerve injuries(PNI) were noted in 17( 24.2%) patients in group A and 20( 28.5%) patients in group B. The surgery was found convenient in Group A with Fibrin Glue repair where it was seen in 32 (91.42%) vs. 20 (57.14%) with p value of 0.02. Duration of repair was significantly high in Group B, with 6.34 ± 0.87 vs. 31.43 ± 8.31 minutes with p values of 0.0001 respectively. The efficacy was seen in 26 (74.28%) vs. 24 (68.57%) with p value 0.68.Conclusion: Fibrin glue repair is a good alternative to micro suture technique in terms of convenience to surgeon and decrease duration for surgery. However, the efficacy was similar with no significant difference in grade of motor recovery in both groups.